Characteristics of power output during supramaximal cycle ergometer exercise in first- and third-grade male Japanese high school cyclists - Nakamura, N. (Journal of Science and Cycling, 2020)
Purpose: The purpose of this cross-sectional study was to clarify if there are differences in optimal load (Lopt; force factor), optimal cadence (Copt; velocity factor), and maximal anaerobic power (MAnP) between first- and third-grade high school cyclists and if Lopt is related to muscle strength.Methods: Forty-three male high school cyclists (first grade: 15.6 ± 0.5 years, n = 20; third grade: 17.3 ± 0.5, n = 23) participated in this study. The MAnP test was conducted at three different loads using an electrically braked cycle ergometer, and MAnP, Lopt, and Copt were determined. The subjects` isokinetic knee extensor and flexor muscle strengths were measured at 180°/sec in an isokinetic dynamometer.Results: The MAnP value of the third-grade cyclists was significantly higher than that of the first-grade cyclists (1116.2 ± 131.8 vs. 946.6 ± 106.5 W, P < 0.01). There was no difference in Copt between the two grades, whereas Lopt was significantly higher in third-grade cyclists than first-grade cyclists (9.4 ± 0.8 vs. 8.2 ± 0.7 kp, P < 0.01). Both muscle strengths were significantly higher in third-grade cyclists than first-grade cyclists. In all subjects, muscle strengths were significantly correlated with Lopt (knee extension and flexion; r = 0.670 and r = 0.466, respectively, P < 0.01).Conclusion: The higher MAnP resulting from greater Lopt in third-grade high school cyclists was related to greater lower limb muscle strength, compared with that of first-grade high school cyclists.